Genomic characterization of selfing in the cyclic parthenogen Daphnia magna. (25th March 2021) - Cornetti, Luca; Fields, Peter D.; Ebert, Dieter
Abstract: Inbreeding refers to the fusion of related individuals' gametes, with self‐fertilization (selfing) being an extreme form of inbreeding—involving gametes produced by the same individual. Selfing is expected to reduce heterozygosity by an average of 50% in one generation; however, little is known about the empirical variation on a genome level surrounding this figure and the factors that affect variation. We selfed genotypes of the cyclic parthenogen Daphnia magna and analysed whole genomes of mothers and selfed offspring, observing the predicted 50% heterozygosity reduction on average. We also saw substantial variation around this value and significant differences among mother–offspring pairs. Crossover analysis confirmed the known trend of recombination occurring more often towards the telomeres. This effect was shown, through simulations, to increase the variance of heterozygosity reduction compared to when a uniform distribution of crossovers was used. Similarly, we simulated inbred line production after several generations of selfing and we observed higher variance in achieved homozygosity when we consider a higher recombination rate towards the telomeres. Our empirical and simulation study highlights that the expected mean values of heterozygosity reduction show remarkable variation, which can help understand, for example, differences among inbred individuals. Abstract : This empirical and simulation study highlights that the expected mean values of heterozygosity reduction show remarkable variation, which can help understand, for example, differences among inbred individuals. This variation is largely determined by the number of crossovers and their spatial distribution along the chromosomes. The crossovers' realistic u‐shaped bimodal distribution, where recombination occurs more often towards the telomeres, yielded significantly higher variance than the uniform distribution model, as recombination suppression around the centromeres generates long stretches of non‐recombinant homozygous or heterozygous regions that increase the variance of heterozygosity reduction.